Effects of Seawater Salinity and Temperature on Growth and Pigment Contents in Hypnea cervicornis J. Agardh (Gigartinales, Rhodophyta). (19th November 2013) - Ding, Lanping; Ma, Yuanyuan; Huang, Bingxin; Chen, Shanwen
Abstract : This study simulated outdoor environmental living conditions and observed the growth rates and changes of several photosynthetic pigments (Chl a, Car, PE, and PC) in Hypnea cervicornis J. Agardh (Gigartinales, Rhodophyta) by setting up different ranges of salinity (25, 30, 35, 40, 45, and 50) and temperature (15, 20, 25, and 30°C). At conditions of culture, the results are as follows. (1) Changes in salinity and temperature have significant effects on the growth of H. cervicornis . The growth rates first increase then decrease as the temperature increases, while growth tends to decline as salinity increases. The optimum salinity and temperature conditions for growth are 25 and 25°C, respectively. (2) Salinity and temperature have significant or extremely significant effects on photosynthetic pigments (Chl a, Car, PE, and PC) in H. cervicornis . The results of this study are advantageous to ensure propagation and economic development of this species in the southern sea area of China.